KAJIAN POTENSI EKONOMI KULINER LOKAL DI DAERAH BOGOR, JAKARTA DAN SOLO - Musa Hubeis (JMB : Jurnal Manajemen dan Bisnis, 2019)
Indonesia is a country rich in natural resources and its potential, namely diverse traditions, cultures and culinary products, more than 13,000 islands (more than 6000 are inhabited islands), more than 700 languages and various cultures. These culinary pro-ducts are usually found on the roadside, exhibitions, or available restaurants that provide Indonesian special menus. From the various types in the cities of Jakarta, Bogor and Solo, it can be seen the level of customer satisfaction that consumes culinary food/ drinks in terms of Tangibles, Reliability, Responsiveness, Assurance and Empathy which are the five quality dimensions in products and services. In practice, this can be simplified or the definition of quality and service quality assessed by consumers. This research was conducted to identify and analysis the level of culinary consumer satisfaction from each of the Research Attributes in the cities of Bogor, Jakarta and Solo and to find out the level of satisfaction of food/beverage culinary in the cities of Bogor, Jakarta and Solo. The location of the study was carried out in the cities of Bogor, Jakarta and Solo. This study uses the qualitative Strengths, Weakneses, Oportunities, and Threats SWOT and Crosstab analysis. The sample of the research used purposive sampling and 30 respondents in Bogor, Jakarta and Solo. The results of the research based on the qualitative SWOT analysis found a strategy to developed competitiveness is making diverse culinary products, expanding the product distribution network, utilizing culinary lovers, improving and promoting, conducting strategic location/sales location selected, innovating on product development, increasing Human Resource knowledge, building coordination and cooperation. Based on the analysis Crosstab by Statistical Package for Social Science (SPPS), it was found that there were actually no differences in customers in terms of individual attributes, and on the other hand the average respondent was very fond of culinary in Bogor, Jakarta, and Solo. The result show local culinary as a sub-sector industy have oportunities contribution income in local economic development in culinary tour.